Online Teaching in the Time of Covid 19-Effectiveness and Challenges - Rucha R. Lohi1 , Nikita Dhahikar2 , Ranjit Ambad3 , Dhruba Hari Chandi4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
India is facing COVID 19 Education Crisis many students have been affected by the closure of schools andcolleges. This has caused a dramatic change in the education with a distinctive shift to e-learning where theteaching is done on digital platforms. Most of the schools and colleges are conducting online classes to copeup with the situation and to save the students from the loss. However it has its own drawbacks like issuesof internet connectivity, availability of required resources, understanding the software application and lackof personal attention, less student attentiveness, etc. This paper studies the effectiveness of online studentsclasses conducted to evaluate the effectiveness of online teaching. It also includes the software applicationsthat can be used to conduct online classes. Online teaching is the future of students.